PENINGKATAN KUALITAS SDM MELALUI SEKOLAH PAMONG DI DESA PAKISAN KABUPATEN BONDOWOSO - Endah Kurnia Lestari; Agus Luthfi; Herman Cahyo Diartho; Fivien Muslihatinningsih; Duwi Yunitasari (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Village development can be achieved if it is balanced with an increase in the quality of human resources for village officials who are qualified and visionary. One of the villages in Bondowoso Regency, namely Pakisan Village, Tlogosari District, has the potential for natural and economic resources that have not been managed properly so that the village is not yet advanced and independent. One of the obstacles that has made Pakisan Village, Tlogosari Subdistrict, not yet advanced and independent is the not yet optimal village development planning system built by village officials. This causes natural and economic potential not to be managed properly. One of the things that is done to realize village development planning is the quality of human resources for village officials who must have a professional and visionary attitude. In reality, there are still many village governments that still have low professionalism and a lack of innovation and creativity. So that the management of village potential is still not optimal. Village potential in Pakisan Village, Tlogosari District, Bondowoso Regency is the strength and capability of the village which can provide benefits if managed properly to improve the welfare of the local community. Support for developing and increasing the capacity of village officials in government management in Pakisan Village, Tlogosari District, Bondowoso Regency also comes from universities, in this case the University of Jember, especially the Institute for Research and Community Service (LP2M). One form of this support is to provide assistance and hold training and discussions as a means to increase the capacity of village apparatus in Pakisan Village, Tlogosari District, Bondowoso Regency who are professional, creative and innovative.